Land map : Manitoba, Southern portion - Manitoba. Department of Mines and Natural Resources (Department of Mines and Natural Resources Manitoba, 1953)
This is a map of Manitoba in 1953 showing Crown and school lands, roads, schools, Indian reserves, forest reserves and national parks. Scale 1:506,880, or 8 miles to 1 inch. Shows Crown and school lands, roads, schools, Indian reserves, forest reserves, national parks, railways, cities and towns. Material digitized as part of an Academic Innovation Fund (AIF), awarded in 2018. For more information see: http://avptl.info.yorku.ca/academic-innovation-fund/ .